Molecular Cloning and Characterization of a Novel Gene Involved in Fatty Acid Synthesis in Brassica napus L. - Gang XIAO; Zhen-qian ZHANG; Rui-yang LIU; Chang-fa YIN; Xian-meng WU; Tai-long TAN; Chun-yun GUAN (Journal of Integrative Agriculture)
Based on the sequence of a novel expressed sequence tag (EST), the full-length cDNA of 1 017 nucleotides was cloned from Brassica napus cv. Xiangyou 15 through rapid amplification of cDNA ends (RACE). The gene was designated as Bnhol34 (HQ585980), encoding a protein of 338 amino acids. BLAST analysis showed no high degree of sequence identity to any known gene. The calculated molecular weight of the Bnhol34 protein was 36.23 kDa, and the theoretical isoelectric point was 8.74. The Bnhol34 was also cloned from a high oleic acid mutant 854-1 through homologous cloning. There was no difference between the two Bnhol34 genes. Bnhol34 was localized in a tissue-specific manner in B. napus, and its expression level was about eight-fold greater in Xiangyou 15 seeds than in 854-1. The promoter region sequences of Bnhol34 were then isolated from Xiangyou 15 and 854-1, and a 93-bp deletion was found to occur in the Bnhol34 promoter region of 854-1. Three abscisic acid-responsive cis-elements (ABRE) were identified in the promoter region of Xiangyou 15. Real-time PCR analyses revealed that exogenous abscisic acid increased Bnhol34 expression by about four-fold in Xiangyou 15 seeds, yet did not change Bnhol34 expression in 854-1. It appeared that Bnhol34 might be abscisic acid insensitive in 854-1.